1999
DOI: 10.1093/jn/129.2.463s
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Very Low Density Lipoprotein: A Two-Step Process of Apolipoprotein B Core Lipidation

Abstract: The liver plays a primary role in lipid metabolism. Important functions include the synthesis and incorporation of hydrophobic lipids, triacylglycerols and cholesteryl esters into the core of water-miscible particles called lipoproteins and the secretion of these particles into the circulation for transport to distant tissues. In this article, we present a brief overview of one aspect of the assembly process of very low density lipoproteins, namely, possible mechanisms for combining core lipids with apolipopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 21 publications
1
52
0
Order By: Relevance
“…Recent data (summarized in Refs. 3,52) support the model that a small apoB-containing lipoprotein of HDL density is the "primordial" particle that results from the MTP-dependent phase of initial lipidation in the ER. These primordial particles can be secreted directly as lipoproteins in the HDL density range or they can be further lipidated within the cell to VLDL density and then secreted.…”
Section: Discussionsupporting
confidence: 70%
“…Recent data (summarized in Refs. 3,52) support the model that a small apoB-containing lipoprotein of HDL density is the "primordial" particle that results from the MTP-dependent phase of initial lipidation in the ER. These primordial particles can be secreted directly as lipoproteins in the HDL density range or they can be further lipidated within the cell to VLDL density and then secreted.…”
Section: Discussionsupporting
confidence: 70%
“…Overexpression of DGAT1 and the ACATs in McA-RH7777 cells offered us the potential to speculate on the mechanism whereby the bulk addition of core lipids is added to nascent apoB-lipoproteins (52,53,62). Interestingly, we found that when cells transfected with DGAT were stimulated with OA, they secreted VLDL with high TG:CE ratios; when cells were transfected with either ACAT1 or ACAT2, they secreted VLDL with closer to equivalent amounts of TG and CE.…”
Section: Effect Of Oleic Acid On the Stimulation Of Apob Secretion Bymentioning
confidence: 77%
“…Several recent studies have supported a model in which the assembly of apoB-containing VLDL particles occurs in two discrete steps (52,53), with the merging of a lipid-poor nascent apoB-lipoprotein and a TG-rich droplet comprising the second step. Our present findings raised the question whether the lipid-rich VLDL secreted would be specifically TG-enriched, regardless of the enzyme that was overexpressed, or alternatively, would have a lipid core reflecting the enzyme that was specifically increased.…”
Section: Effect Of Oleic Acid On the Stimulation Of Apob Secretion Bymentioning
confidence: 95%
“…Many of the synthesized lipids are exported from the liver in the form of apolipoprotein-containing particles known as very low density lipoproteins (VLDLs), precursors of low-density lipoproteins. The VLDLs are composed of a nonpolar core of triglycerides and cholesteryl esters surrounded by a monolayer amphipathic coating of protein, phospholipids, and cholesterol (14,15). VLDLs are formed in the luminal space within the endoplasmic reticulum (ER), whereas the lipids that are required for their formation are synthesized on the cytosolic side of the ER membrane (16).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%